Effect of Extracts of Frozen-Thawed Heart Fragments on Rats - Rohoza, L.A.; Чиж, М.О.; Galchenko, S.Ye; Sandomirsky, B.P. (Probl Cryobiol Cryomed. 2013. 3(1): 91-8., 2013)
The investigation was performed to reveal the influence of the extracts of frozen-thawed heart fragments of pigs and newborn piglets administered to young and aged rats on an organism in general and heart in particular. Administration of the extracts to young animals during 28 days was shown to increase the number of nuclei in the heart muscle unlike the mature rats, but did not affect the rate of changes in the weight of animals and their hearts. No effect of extracts on blood morphology and heart electrophysiological parameters was found. ////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////// В роботі вивчено вплив екстрактів кріоконсервованих фрагментів серця свиней та новонароджених поросят на організм в цілому та серце молодих і статевозрілих щурів. Встановлено, що введення екстрактів протягом 28 діб призводить до збільшення щільності ядер в м’язі серця у молодих тварин, на відміну від статевозрілих, але не впливає на швидкість зміни маси тварин та їх сердець. Показано, що екстракти не впливають на морфологічну картину крові та електрофізіологічні показники роботи серця тварин.
Влив екстрактів кріоконсервованих фрагментів серця на організм щурів
Rohoza LA, Chizh MO, Galchenko SY, Sandomirsky BP. Effect of Extracts of Frozen-Thawed Heart Fragments on Rats. Probl Cryobiol Cryomed. 2013. 3(1): 91-8. http://cryo.org.ua/journal/index.php/probl-cryobiol-cryomed/article/view/15
Keywords: extracts; peptides; heart; organism; pigs; piglets; rats; екстракти; пептиди; серце; організм; свині; поросята; щури